2019
DOI: 10.2147/hiv.s204985
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comorbidities in a sample of adults with HIV in Puerto Rico: an exploratory study</p>

Abstract: Background Puerto Rico is among the areas with the highest estimated rates of people living with HIV in the United States. Despite the epidemiologic data available, there is limited real-world information that can help understand the comorbidities of people with HIV. In this study, we describe common comorbidities among adults with HIV attending treatment clinics in Puerto Rico. Methods An exploratory, retrospective, cross-sectional study was conducted at five HIV clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Another analysis by Rodriguez-Diaz et al, [16] reported that 19.2% of Puerto Ricans with HIV aged 50 and above also have depression. These figures for Latinxs with depression, along with the surge of depression in HIV-infected individuals, align with our findings as the average age of our subjects was 53 years, and 24.3% were diagnosed with the mental health disorder.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another analysis by Rodriguez-Diaz et al, [16] reported that 19.2% of Puerto Ricans with HIV aged 50 and above also have depression. These figures for Latinxs with depression, along with the surge of depression in HIV-infected individuals, align with our findings as the average age of our subjects was 53 years, and 24.3% were diagnosed with the mental health disorder.…”
Section: Discussionmentioning
confidence: 98%
“…While ART has indisputable benefits, it does not prevent the development of comorbidities and disruptions often seen in those infected with HIV, such as cardiovascular, motor, and cognitive alterations [16]; in ART-treated individuals, the progression of their cognitive system disruption as a result of HIV is slowed, but cannot be aggregately prevented [15]. As is the case with diminishing cognition, motor and gait changes are also intransigent and pervasive in those with HIV, comprising a wide range of manifestations including the reduction or cumulative loss of fine motor skills, balance, and locomotion, as well as the induction of unsteady and slow gait, hyperreflexia, and bradykinesia [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 PR experiences a syndemic of overdoses with opiates, HIV, and HCV, 11,12 and, overall, policies to curb the HCV epidemic in the archipelago are lacking. 13,14,15,16 In clinic-based samples of people with HIV, it has been documented that 13.2% have also received a diagnosis of chronic Hepatitis C. 17 Further, while treatment and cure for HCV are available, the knowledge about access to, retention in, and success of care for people with HIV and HCV coinfection is limited. 18 People with HIV and HCV coinfection may have a faster disease progression that requires better-articulated interventions.…”
Section: Introductionmentioning
confidence: 99%
“…En un estudio en Puerto Rico, donde se revisaron un total de 250 (179 hombres; 71 mujeres) registros médicos, con un edad media de los participantes de 47.9 años y, en promedio, habiendo estado viviendo con el VIH durante 9 años, la mayoría (97.6%) tenía al menos una comorbilidad, siendo la dislipidemia e hipertensión las más comunes(30).…”
unclassified